Management of the motivation and incentive system of work of teachers - Kharchenko A. I., Antropova R. M., Kokhan N. V. (Upbringing and education: theory, methods and practice, 2018)
the paper is devoted to the main issues related to the management of the motivation and incentive system of the work of pedagogical workers. The stable motivation and incentive system contributes to raising the professional level, developing the actual competencies of the pedagogical sphere.
Keywords: мотивация; управление; стимул; motivation; педагогические работники; management; система стимулирования; incentive; формы оплаты труда; принципы оплаты труда; the motivation and incentive system; pedagogical workers; forms of labor remuneration; principles of labor remuneration